Influence of Some Innovation Attributes on the Adoption of Growing Sunflower in Rahad Scheme - M. Abdel Rahman, Ahmed; E. Mohamed, Ibrahim; S. Gangi, Ali (Gezira Journal of Agricultural Science; Vol 2 No 1 (2004), 2021)
The vital economic importance of sunflower as one of the oil crops encouraged its introduction to the Sudan in the last twenty years. The production of sunflower crop began in Rahad scheme, as in other irrigated areas in the country, in 1992/93 growing season. Field survey was used to collect data from 100 sunflower growers (adopters) in Rahad Scheme (block 10) in 2002/2003 growing season selected from a total population of 1000-1100 farmers by using the simple random sample technique. An equal number of non-adopters was selected for comparison. The total number of interviewed farmers was 200. The collected data was statistically analyzed using the chi-square test. The results showed significant association (dependency) between adoption of growing sunflower (the innovation) and some of its attributes: Relative advantage on perceived production cost and income, compatibility with farmers need as cash crop and animal feed, complexity associated with use of technical package for sunflower. From the findings of this study, we can conclude that the adoption of this crop was dependent on some innovation attributes and the results were expected to reveal factors influencing adoption of the crop. The authors recommend that more attention should be given by agronomists to this crop in order to improve the yield of the crop and extension services should design special programs for the crop to promote its rate of adoption.